Science Education for Social Justice Using the Knowledge-Building Communities Model (LEARNing Landscapes, 2014)
In this article, we explore the connections to, and potential contributions of, the knowledge-building communities (KBC) model to science education for social justice. We examine the principles and design features that underpin the KBC model and reflect on the ways in which they are consistent with, and support some of, the important dimensions of science education for social justice, including: 1) building on students’ ideas and interests; 2) encouraging and valuing the inclusion of diverse perspectives; 3) collaborative participation and community; and 4) fostering engagement with the outside world.
Keywords: knowledge-building communities (KBC); science education; social justice; engagement; diversity; inclusion; collaborative participation